Representation and Reception : Women in the Copenhagen Bohun Hours Ms. Thott 547 4º - Vidas, Marina (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2015)
Marina Vidas: Representation and reception. Women in the Copenhagen Bohun Hours. Ms. Thott 547 4º This article presents and analyzes depictions of women in the Copenhagen Bohun Hours (Copenhagen, Royal Library, Ms. Thott 547 4º), an exquisitely illuminated fourteenth-century English manuscript, made for a young female member of the Bohun family, and focuses on meanings images could have had for their primary viewer. The representations which are examined are of: the book owner, the Virgin Mary, shown on nine of the fully illuminated folia, St. Elizabeth, Mary Magdalene, Job’s wife, a group of nuns as well as of three mothers who appear in the bas-de-pages. Firstly, it is argued that the painted portrait of the book owner is flattering in its presentation of the subject’s beauty, status and character. Attention is drawn to the fact that in her portrait, the book owner resembles the Virgin shown on the same folio. Secondly, it is suggested that the representations of the armorials of the heiress’s natal family, dominant in the manuscript, are evidence of pride in her noble lineage and her succession to the family titles as countess in her own right while the arms of the crown, depicted on her surcoat in her portrait and on one of the fully-illuminated folios, proclaim her royal connections. Thirdly, representations of holy women are discussed and it is suggested that they offered the viewer a variety of relevant role models and experiences to admire, inspire, and imitate. It is also proposed that some of the tales and scenes in the bas-de-pages could have had a cautionary purpose. Finally, it is observed that there is a substantial interest not only in individual women but a more general preoccupation with women’s relationships with the divine, with children and with other women.